If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -5) = 7y + 1 Reorder the terms: 3(-5 + y) = 7y + 1 (-5 * 3 + y * 3) = 7y + 1 (-15 + 3y) = 7y + 1 Reorder the terms: -15 + 3y = 1 + 7y Solving -15 + 3y = 1 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -15 + 3y + -7y = 1 + 7y + -7y Combine like terms: 3y + -7y = -4y -15 + -4y = 1 + 7y + -7y Combine like terms: 7y + -7y = 0 -15 + -4y = 1 + 0 -15 + -4y = 1 Add '15' to each side of the equation. -15 + 15 + -4y = 1 + 15 Combine like terms: -15 + 15 = 0 0 + -4y = 1 + 15 -4y = 1 + 15 Combine like terms: 1 + 15 = 16 -4y = 16 Divide each side by '-4'. y = -4 Simplifying y = -4
| 48=34-32(x-3) | | x(5x-2)+x(3x-2)=(8x+5)(x-3) | | x+2x+3=72 | | .50d-4=7 | | x^2-32X+252=0 | | 93.96=4.7p+8.7p-2.60 | | 9x+7=6x+14 | | f(5)=2x | | 2x+10=40-3x | | 2(4m+n)-2n= | | sqrt(x+5)=x^2-5 | | 6x+8y = 7 | | 10/2*5-1+3= | | 0.96-0.8M=-12.6 | | -5=-3x+y | | w+2+4w+10= | | (X-5)(3x-1)=0 | | -5(6-x)+4=6-7(x+2) | | 46+38+24w=180 | | 3x+7=17-2x | | 8x^3-6x^2-14x= | | 3x-11=26 | | (4m-1)(m+3)=0 | | -3(3p+3)-2(3-11p)=3(7+4p) | | 125m-75m+48000=50750-200m | | 3(x-24)=0-2(x-4) | | 4-(3a+4)=7 | | 2.7and+4.1=36.5 | | 2x+y+xi+yi=5+4i | | 6v+12=180 | | 6r+5=49 | | 2x+8+5=3x-1 |